2022
DOI: 10.1186/s13045-022-01329-w
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of SARS-CoV-2 spike protein on retrieved thrombi from COVID-19 patients

Abstract: The pathophysiology of COVID-19-associated coagulopathy is complex and not fully understood. SARS-CoV-2 spike protein (SP) may activate platelets and interact with fibrin(ogen). We aimed to investigate whether isolated SP can be present in clots retrieved in COVID-19 patients with acute ischemic stroke (by mechanical thrombectomy) and myocardial infarction. In this pilot study, we could detect SP, but not nucleocapsid protein, on platelets of COVID-19 patients’ thrombi. In addition, in all three COVID-19 throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Although SARS-CoV-2 proteins are synthesized in the cytosol, some viral proteins are also detectable in the nucleus, including Nsp1, Nsp5, Nsp9, Nsp13, Nsp14, and Nsp16 [ 71 ]. This becomes important as recent research has shown that the S protein also localizes in the nucleus and inhibits DNA damage repair by impeding key DNA repair protein BRCA1, and recruitment of 53BP1 to the damage site [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although SARS-CoV-2 proteins are synthesized in the cytosol, some viral proteins are also detectable in the nucleus, including Nsp1, Nsp5, Nsp9, Nsp13, Nsp14, and Nsp16 [ 71 ]. This becomes important as recent research has shown that the S protein also localizes in the nucleus and inhibits DNA damage repair by impeding key DNA repair protein BRCA1, and recruitment of 53BP1 to the damage site [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we recently described SP in a retrieved thrombus from MCA of one of the two AIS patients with COVID-19 having detectable serum SP level ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…We recently detected the SP, but not the nucleocapsid protein (NP) or the SARS-CoV-2 RNA, in thrombi retrieved from the middle cerebral artery (MCA) of three COVID-19 patients with large vessel occlusion related acute ischemic stroke (AIS) and in a thrombus retrieved from the coronary artery of a COVID-19 positive patient with acute myocardial infarction, supporting a potential role of sSP, independently of the whole virus, in clot formation ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are three major system biology findings of COVID-19 that need to be explained by molecular events. Vascular clots, particular micro clots in pulmonary vessels [23,24], enlarged arteries with echogenic, probably thickened-colloidal, blood flow [25] and a histochemical finding of SARS-CoV-2 virions, or at least Spike protein, can be found at the core of the thrombi [24,26].…”
Section: Covid-19 Vascular Pathologiesmentioning
confidence: 99%